KAJIAN PENGARUH U-TURN TERHADAP TINGKAT PELAYANAN JALAN G. OBOS KOTA PALANGKA RAYA - ., RISWANDI; ., Salonten; Riani, Desi (Program Studi Teknik Sipil Universitas Narotama, 2022)
On Jalan G. Obos, Palangka Raya City, there are several median opening points (u-turns) that experience congestion and long queues due to traffic volume and high side barriers. This research is expected to provide useful solutions and suggestions to improve road services at the intersection segment of Galaxy Raya Road-G. Obos Road and Temanggung Tilung Road-G. Obos Road, Palangka Raya City. Based on the results of the research at the research location, the largest traffic flow volume before the u-turn was 1491.6 skr/hour and after the u-turn was 817.25 skr/hour, so that the value for the level of road service before the u-turn got an F value. while the level of road service after the u-turn gets a C value.